2013
DOI: 10.1177/1932202x12472491
|View full text |Cite
|
Sign up to set email alerts
|

A Sample of Gifted and Talented Educators’ Attitudes About Academic Acceleration

Abstract: Despite extensive research supporting its use, including the 2004 publication of A Nation Deceived, acceleration is an underutilized strategy for meeting the academic needs of gifted and talented students. Parents’ and educators’ attitudes and beliefs about acceleration influence the extent to which it is implemented in schools. This study investigated gifted and talented educators’ attitudes toward acceleration using a 7-point rating scale measuring concerns about acceleration, beliefs about acceleration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 71 publications
1
60
0
1
Order By: Relevance
“…The factor structure of teachers' beliefs found in our study is in accordance with previous results on teachers' concerns (Hoogeveen et al, 2005;Southern et al, 1989) as the content was similar, and the number of factors we found was limited as well. Our factors also reflect the main dimensions reported by Siegle et al (2013) with the exception that in our study, concerns about students being younger than their peers did not load on a separate factor but were associated with beliefs about students' social integration; concerns about students missing out on extracurricular activities were associated with beliefs about academic development and the additional time needed to catch up in our study. Furthermore, teachers' beliefs about students' social integration seemed to be particularly relevant for teachers' acceptance of grade skipping.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The factor structure of teachers' beliefs found in our study is in accordance with previous results on teachers' concerns (Hoogeveen et al, 2005;Southern et al, 1989) as the content was similar, and the number of factors we found was limited as well. Our factors also reflect the main dimensions reported by Siegle et al (2013) with the exception that in our study, concerns about students being younger than their peers did not load on a separate factor but were associated with beliefs about students' social integration; concerns about students missing out on extracurricular activities were associated with beliefs about academic development and the additional time needed to catch up in our study. Furthermore, teachers' beliefs about students' social integration seemed to be particularly relevant for teachers' acceptance of grade skipping.…”
Section: Discussionmentioning
confidence: 58%
“…Croft and Wood's (2015) model of the professional development of educators around accelerative strategies highlights how important it is for teachers to challenge existing attitudes and to inform themselves about research-based findings on acceleration. Whereas educators' attitudes toward accelerative strategies seem to be falling more in line with empirical findings about the effectiveness of these techniques, educators appear to remain somewhat reluctant to grade skipping (McCoach & Siegle, 2007;Siegle et al, 2013). The purpose of the present study was to describe the current perspectives on grade skipping in a sample of German secondary teachers.…”
Section: Explaining the Odds Of Teachers' Recommendations For Grade Smentioning
confidence: 92%
See 3 more Smart Citations